Milk fed : a novel - Broder, Melissa (Scribner, an imprint of Simon & Schuster, 2021)
"Rachel is twenty-four, a lapsed Jew who has made calorie restriction her religion. By day, she maintains an illusion of existential control, by way of obsessive food rituals, while working as an underling at a Los Angeles talent management agency. At night, she pedals nowhere on the elliptical machine. Rachel is content to carry on subsisting--until her therapist encourages her to take a ninety-day communication detox from her mother, who raised her in the tradition of calorie counting. Early in the detox, Rachel meets Miriam, a zaftig young Orthodox Jewish woman who works at her favorite frozen yogurt shop and is intent upon feeding her. Rachel is suddenly and powerfully entranced by Miriam--by her sundaes and her body, her faith and her family--and as the two grow closer, Rachel embarks on a journey marked by mirrors, mysticism, mothers, milk, and honey."--Dust jacket flap.